Clinical importance of renal calyceal microlithiasis in children. Issue 6 (December 2013) - Bilge, Ilmay; Yilmaz, Alev; Kayiran, Sinan M; Emre, Sevinc; Kadioglu, Alev; Yekeler, Ensar; Sucu, Aysegul; Sirin, Aydan
Abstract Background Renal calyceal microlithiasis refers to a hyperechogenic spot in renal calyces <3 mm in diameter detected on renal sonography. These spots possibly represent the first step in calculus formation. The aim of this study was to analyze the clinical presentation, predisposing factors, prognosis and clinical importance of these hyperechogenic spots in renal calyces, renal calyceal microlithiasis, during childhood. Methods The data of 292 children (135 girls, 157 boys) with microlithiasis diagnosed between January 1998 and December 2010 were evaluated retrospectively. Demographic data, serum biochemistry, urinary metabolic factors, and renal sonography results were obtained from patient files. A total of 228 patients were re‐evaluated at least 6 months after the first observation of renal calyceal microlithiasis and at 6–12 month intervals thereafter. Results Mean age was 16.8 ± 14.9 months, and mean follow‐up duration was 14.6 ± 5.9 months. Presenting symptoms were abdominal or flank pain (41.1%), hematuria (35.6%), dysuria (24.7%) and urinary tract infection (34.6%). Previous ultrasounds were normal in 35% of the children. Metabolic and anatomic abnormalities were found in 55.5% and 17.8%, respectively. Hypercalciuria was the most common metabolic abnormality (88.9%). Among 228 patients who had been re‐evaluated, microlithiasis disappeared in 37.7%; decreased in number or size in 23.7%; progressed to renal stone formation in 10.6%; increased in number of microlithiasis in 19.0%; and remained unchanged on radiology in 9.0%. Conclusion Renal calyceal microlithiasis represents a spectrum of clinical situations and underlying metabolic abnormalities that need further investigation in children.